A Monitoring System for Chronic Diseases - Chen, Rina; Mantel, N.; Connelly, R. R.; Isacson, P. (Methods of Information in Medicine, 1982)
A statistical technique for detecting an increase in the rate of a chronic disease is proposed. The technique is based on the time interval between consecutive diagnoses. An increase is considered significant when all the intervals are shorter than the appropriate critical duration. The technique was applied to data collected by a state-wide cancer registry and results are illustrated for two types of cancer.
Keywords: Monitoring System; Poisson Distribution; Exponential Distribution; Epidemics